2019
DOI: 10.1177/1178223419830982
|View full text |Cite
|
Sign up to set email alerts
|

Hematologic Malignancies of the Breast: A Contemporary Series Investigating Incidence, Presentation, Accuracy of Diagnosis on Core Needle Biopsy, and Hormone Receptor Expression

Abstract: Background: Distinguishing breast hematologic malignancies in core needle biopsies from other entities can be challenging. Misclassification as a breast carcinoma could result in inappropriate treatment. The aim of this study was to characterize the types, incidence, and helpful diagnostic features of hematologic malignancies of the breast. Design: All hematologic malignancies of the breast diagnosed at our institution from 2004 to 2017 were identified. Clinical notes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Guilbert et al reported a similar proposal. 8 Yoneyama et al reported a similar case, and they highlighted several characteristics, including conspicuous apoptosis, marked nuclear rays due to crushing, and polymorphism in tumor cells, that distinguish breast cancer from PBL. 5 Lin et al also identified several characteristics as findings suspicious of lymphoma, such as lack of in situ lesions, frequent individual karyorrhectic cells, lymphoepithelial lesions, and cellular discohesiveness.…”
Section: Discussionmentioning
confidence: 97%
“…Guilbert et al reported a similar proposal. 8 Yoneyama et al reported a similar case, and they highlighted several characteristics, including conspicuous apoptosis, marked nuclear rays due to crushing, and polymorphism in tumor cells, that distinguish breast cancer from PBL. 5 Lin et al also identified several characteristics as findings suspicious of lymphoma, such as lack of in situ lesions, frequent individual karyorrhectic cells, lymphoepithelial lesions, and cellular discohesiveness.…”
Section: Discussionmentioning
confidence: 97%
“…This pattern can also be noted in chronic lymphocytic lymphoma. According to Guilbert et al, [8] diabetic mastopathy shows periductular and perivascular infiltrate with sparing of intervening stroma which is dense collagenous. In contrast, intervening stroma is involved with lymphocytic infiltrate in chronic lymphocytic lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…However complete absence of cohesion, lack carcinoma in situ component along with absent receptor expression should alert pathologist for some other entity. [8] Likewise lobular carcinoma with its typical Indian file pattern of infiltration is a close mimic for lymphoma. However, lobular carcinoma in general express strong ER positivity in 95% of cases [9] and its absence in a suspected case of lobular carcinoma should be taken as a lead for further evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Lobular carcinoma of the breast infiltrates can present as single cells and the tumor cells could mimic lymphocytes [1]. Cyclin‐D1, a well‐known oncogene, is overexpressed in approximately half of breast cancers [2–4].…”
Section: Figurementioning
confidence: 99%
“…A 60-year-old female presented with fatigue and pinpoint bruising on her legs and abdomen. Labs were consistent with severe pancytopenia and bone marrow aspiration and biopsy were performed to investigate the cause; however, flow cytometry studies could not be done due Lobular carcinoma of the breast infiltrates can present as single cells and the tumor cells could mimic lymphocytes [1]. Cyclin-D1, a well-known oncogene, is overexpressed in approximately half of breast cancers [2][3][4].…”
mentioning
confidence: 99%